X-band polarization conversion radome based on dielectric-embedded metamaterial elements for high-power microwave application - Feng Yan; Chengwei Yuan; Qinghe Zhuang; Meng Yang; Wensen Yang; Zhengfeng Xiong (AIP Advances)
A novel polarization conversion radome based on dielectric-embedded metamaterial elements is proposed to decrease the size of antenna profiles. This radome is composed of two kinds of interlaced dielectric-embedded metamaterial elements to realize the polarization conversion and beam deflection. The structures and characteristics of two types of dielectric-embedded metamaterial elements have been studied and analyzed. By selecting an appropriate dielectric material and applying periodic boundary conditions to optimize these two kinds of dielectric-embedded metamaterial elements, the radome made up of these metamaterial elements eventually is mounted atop a square horn antenna. Simulation results indicate that the antenna radome enables the horn antenna to achieve polarization conversion and beam deflection at the operating frequency. The maximum beam deflection angle can be 29° within a gain reduction of 1 dB, while the axial ratio remains below 1.5 dB and the reflection coefficient continuously remains below −22 dB. Moreover, the power-handling capacity of each metamaterial element within the radome is above 60 kW.